Tight sandstone fluid detection technology based on multi-wave seismic data - Yutan Dou; Daxing Wang; Mengbo Zhang; Fei Li; Guanghong Du; Yonggang Wang; Yuhua Zhao; Feng Liu; Yan Huang; Jie Zhang; Xiaojie Cui; Ligang Huang; et al. (Open Geosciences)
The SX area of the Ordos Basin in China is characterized by small thickness and considerable lateral variation of the reservoir, and high heterogeneity. It is difficult to identify gas and water by conventional P-wave seismic data without fully utilizing reservoir P-wave and S-wave information. Therefore, this study forms a series of seismic fluid detection technologies based on multi-wave seismic data, including the multi-wave “bright spot” feature analysis, multi-wave amplitude ratio technique, multi-wave amplitude versus offset analysis, multi-wave matched compression correlation analysis, and multi-wave pre-stack simultaneous inversion. The combined application of P- and S-waves facilitates visualized identification of fluids and improves the success rate of seismic prediction of underground gas-bearing features. The multi-wave interpretation technology series for low-permeability lithological gas reservoirs formed in this area has achieved a transformation from qualitative interpretation to quantitative prediction, and from lithological identification to fluid detection. These technologies have achieved significant geological results in the SX area.